Use of Lumbar Perforator Recipient Vessels for Salvage Chest Wall Reconstruction: A Case Report. Issue 3 (March 2016) - Sillah, Nyama M.; Shah, Jinesh; Fukudome, Eugene; Lin, Samuel J.
Abstract : Summary: Abdominal-based free flaps are commonly used for breast reconstruction, and the internal mammary or thoracodorsal vessels are typically used as recipient sites. Conversely, free tissue transfer is less commonly used for chest wall reconstruction in the setting of chest wall recurrence, in part, because of a paucity of recipient vessels. Here, we describe a case of a 68-year-old female smoker with metastatic breast cancer, who presented with a chest wall recurrence. There was a large area of chronic ulceration with foul smelling drainage, in addition to radiation-induced tissue injury, and palliative resection was performed. The area was reconstructed with a free transverse rectus abdominis myocutaneous flap using lumbar perforators as recipient vessels, because conventional recipient sites were unavailable because of scarring from radiation and residual tumor. This case demonstrates that uncommon recipient vessels such as lumbar perforators may allow for successful palliative chest wall reconstruction. We hypothesize that the tumor burden, previous surgeries, and radiation may have rendered the recipient field relatively ischemic, thereby inducing hypertrophy of the lumbar perforators, similar to a delay phenomenon.